Behaviour of recurving cyclonic storms in Arabian Sea as a response to atmospheric interactions - SHYAMALA, B.; SUDEVAN, S.; SHINDE, G. M.; BURTE, M. D. (MAUSAM, 2001)
During the year 1998, Arabian sea witnessed two distinct and unusual cycsystems. The very severe cyclonic storm of June 1998 was the most severe storm since last fifteen years as far as Arabian Sea systems are concerned; while October 1998 system was unique for, Its unusual and sudden easterly track after almost touching Saudi Arabia coast, (ii) Very high speed of movement and (iii) Interaction and merger with another vortex present in Arabian Sea off Saurashtra coast. This study is an attempt to understand the peculiar behaviour of the systems in Arabian sea which do not intensify beyond cyclone stage or even show a tendency to weaken before crossing coast as a response to atmospheric interactions. All the cyclonic systems in Arabian Sea since 1975 (Satellite era) have been examined in detail and the main findings of the study are : (i) Interaction between cyclonic disturbances of different intensities simultaneously present, appears to be the key factor in determining the further intensification or not of the systems. (ii) Track prediction for the systems upto marginal cyclone stage appears to be governed mainly by middle level atmospheric forcing. (iii) Upper level wind steering is found to be important for movement of systems from severe cyclonic storm stage onwards. The above results have direct relevance to operational cyclone forecasting.